北京地区大气污染物源区特征及与重污染过程的关系 - Zou, Qingqing; Cai, Xuhui; Guo, Mengting; Song, Yu; Zhang, Xiaoling (Beijing da xue xue bao, 2018)
Potential source area (footprint) related to air pollution of Beijing is investigated. Long-term modeling of meteorological fields is carried out by WRF model, from 2000 to 2014. A backward dispersion footprint model is used to derive hourly footprint using these meteorological data. Long-term mean source area is obtained as well as its seasonal variation. Heavy air pollution episodes in winter and autumn are selected from air pollution index (API) data in the period from 2000 to 2012. Relationship between air pollution and its potential source area is discussed. Results show that daily mean footprint varies both by its pattern and direction, indicating strong temporal variation of the source areas for Beijing. Long-term mean source area for Beijing is shaped like a triangle, and the southwest branch is the strongest, the other two are in the east and north. Beijing locates in the middle to norther position of the triangle. Seasonal variation of the mean source area show enhancement in the southwest and south